PENERAPAN KOLABORASI PERKULIAHAN SEBAGAI UPAYA MENINGKATKAN KOMPETENSI PEDAGOGIK DOSEN DAN PRAKTISI MENGAJAR MATA KULIAH ETIKA PROFESI - Qomariyah, Ismi Nurul; Sari, Nila Kartika; Hidayati, Permata Ika (Universitas Tribhuwana Tunggadewi, 2023)
The purpose of this article was to discusses the application of lecture collaboration as an effort to improve the pedagogical competence of lecturers and teaching practitioners in the Professional Ethics course in the Biology Education Study Program. The research method used is classroom action research, which involves a cycle of planning, implementing, observing, and reflecting in order to improve teaching practices. This research was conducted in the context of the Biology Education Study Program, involving lecturers and teaching practitioners as research subjects. The classroom action research cycle consists of the stages of planning lecture collaboration, implementing lecture collaboration, observing the process and results of collaboration, and reflection to formulate subsequent improvements. The results showed that the application of lecture collaboration was effective in improving the pedagogic competence of lecturers and teaching practitioners. Collaboration allows them to share experiences, knowledge, and effective teaching strategies. In the context of Professional Ethics courses, lecture collaboration also increases student involvement and motivation in learning. These findings support the study's hypothesis and are also in line with the related literature on the benefits of collaboration in education. The implication of this research is the importance of implementing lecture collaboration as an effective teaching strategy in improving the pedagogical competence of lecturers and teaching practitioners, especially in the Professional Ethics course in the Biology Education Study Program